2015
DOI: 10.33549/physiolres.933213
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Co-Medication on the Pharmacokinetic Parameters of Phenobarbital in Asphyxiated Newborns

Abstract: Phenobarbital is an anticonvulsive drug widely used in newborns with hypoxic-ischemic encephalopathy. The objective of our study was to describe possible effect of frequently co-administered medications (dopamine, dobutamine, norepinephrine, furosemide, phenytoin, and analgesics) on the phenobarbital pharmacokinetics in full term newborns with hypoxic-ischemic encephalopathy. Phenobarbital pharmacokinetic parameters (standardized intravenous loading dose was 10-20 mg/kg, maintenance dose 2-6 mg/kg/day) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…33 None of the included studies measured the serum levels of phenobarbital metabolites so no final conclusions can be drawn about metabolism. [34][35][36][37][38][39] About 66% of neonates with HIE and seizures respond to phenobarbital. 34 35 Pokorná et al 36 observed decreased clearance during TH, although these changes were not statistically significant (table 2b).…”
Section: Phenobarbitalmentioning
confidence: 99%
See 2 more Smart Citations
“…33 None of the included studies measured the serum levels of phenobarbital metabolites so no final conclusions can be drawn about metabolism. [34][35][36][37][38][39] About 66% of neonates with HIE and seizures respond to phenobarbital. 34 35 Pokorná et al 36 observed decreased clearance during TH, although these changes were not statistically significant (table 2b).…”
Section: Phenobarbitalmentioning
confidence: 99%
“…This suggests that disease severity is a more prominent covariate of phenobarbital clearance compared with TH. 36 Furthermore, concomitant dobutamine administration also had an effect on phenobarbital clearance (although the authors suspect this was an artefact of the small sample size 39 ).…”
Section: Phenobarbitalmentioning
confidence: 99%
See 1 more Smart Citation
“…Phenobarbital is one of most frequently administered anticonvulsive drugs in pediatric patients due to its well-established efficacy, the availability of an injectable dosage form, and its additional beneficial sedative effect (8). Monitoring serum phenobarbital concentrations is often routinely performed to achieve safe and effective individual therapy (9,10). Despite its widespread use, there is insufficient information on the potential impact of ECMO on the pharmacokinetics of phenobarbital.…”
mentioning
confidence: 99%
“…The 95% confidence intervals (95% CI) for medians were calculated by the Bonett and Price method 11. The possible impact of anticonvulsive co-medication on levetiracetam pharmacokinetic parameters was evaluated using the Mann-Whitney U-test as described previously 12. A linear regression model was used to evaluate the relationships between levetiracetam pharmacokinetic parameters with continuous variables.…”
Section: Methodsmentioning
confidence: 99%